Green and roasted coffee antiradical activity stability in chemical systems - M. Daglia; A. Papetti; G. Gazzani (Czech Journal of Food Sciences, 2004)
The stability to storage at different temperature and oxygen exposure of green and roasted coffee either as coffee beans or as ground coffee antiradical activity, was evaluated. The results showed that the coffee solution antihydroxyl radical activity was constant, independently from the coffee species, from the roasting process, and moreover from the type of storage conditions, suggesting that temperature and oxygen exposure did not affect this antiradical activity. With regard to antiperoxyl radical activity, all green coffee solutions showed remarkable and stable activity. Conversely, the roasted coffee beans and roasted and ground coffee antiperoxyl radical activity started to increase after three month of storage, suggesting that Maillard reaction products affect the stability of such antiradical property.